STUDI KERAGAMAN JENIS, KANDUNGAN GIZI ESENSIAL DAN KALSIUM OKSALAT DIOSCOREA DI PULAU BALI DAN LOMBOK - Wibawa, I Putu Agus Hendra; Kurniawan, Agung; Adjie, Bayu (Center for Plant Conservation Bogor Botanic Garden, Indonesian Institute of Sciences, 2011)
Dioscorea tuber has many benefits, for example as food or as traditional medicine. The high carbohydrate and protein contents make this plant suitable as a food. However, the presence of crystal oxalate, that causes irritation is an disadvantage aspect on the development of this species. Both of wild and cultivated species will assure the gene flow which is important in efforts to improve the tuber quality should be examine further. This research aimed to observe the biodiversity of Dioscorea in Bali and Lombok, to recognize the utilization and to reveal their nutrients (carbohydrate, protein and fat) and also the contents of calcium oxalate. The results showed that there are five Dioscorea spesies, namely Dioscorea alata L. (ubi) (11 cultivars), Dioscorea esculenta (Lour.) Burkill (ubi aung), Dioscorea hispida Dennst. (gadung), Dioscorea bulbifera L. and Dioscorea pentaphylla L. The highest carbohydrate content (87,42% ) is found in D. alata (ubi ungu cultivar) from Lombok, while the highest protein content (5,05%.) is found in D. alata (ubi dadap cultivar) from Singaraja, Bali. Furthermore, the highest percentage of fat content (0,85%) is found in D. bulbifera from Karangasem, Bali, whereas the high quantity of glaucomannan (44,52%.) id found in D. pentaphylla from Tabanan, Bali, while D. esculenta from Jembarana, Bali has the highest calcium oxalate (0,57%), and D. alata (ubi injin cultivar) from Karangasem, Bali has the least calcium oxalate (0,18%).